UV Photodetector based on Mg-doped GaN Thin Films Prepared by Sol-gel Spin Coating - Amin, Nurfahana Mohd; Ng, Sha Shiong (2017)
In this work, sol-gel spin coated 2 % of magnesium (Mg) doped gallium nitride (GaN) thin films grown on AIN sapphire substrate was reported. The structural, lattice vibrational, and electrical properties of the deposited films were investigated and compared. X-ray diffraction results show that the hexagonal wurtzite structure with preferred orientation of GaN(002). The Raman active phonon modes of the wurtzite GaN correspond to the E2(high) and A1(LO) at 568 em 1 and 733 em 1 phonon modes of the hexagonal GaN were observed, while a broad peak attributed to the Mg-related lattice vibrational mode was detected at 669 em 1. Hall effects results show that the resistivity of 0.1397 0 em for the Mg-doped GaN. The carrier concentration and hall mobility of 1.77 x 1018 cm3 and 6.04 cm2/Vs were obtained. Besides, the characteristics of dark and photocurrent of the ultraviolet (UV) detector and the UV photoresponse of the detector were investigated. The measurements were conducted under dark and UV illuminations. The current-voltage (1-V) characteristics of the Mg doped GaN-based UV photodetector exhibits tile Schottky behaviour. Lastly, the ideality factor and Schottky barrier heights were calculated using thermionic emission theory.